The Role of Social Capital in Social Solidarity Initiatives During the Covid-19 Pandemic in Egypt - Baraka, Nada Moustafa (AUC Knowledge Fountain, 2021)
This qualitative study aimed at studying internal social cohesion in the Egyptian society during Covid-19 pandemic. In our research the notion of social capital acted as a measure of community resilience that was present in the Egyptian social solidarity scene during the peak of the Covid-19 pandemic. The focus is on voluntary associations that mobilize resources to help those in need, often relying on social media for outreach. The main research question is thus: “To what extent did social solidarity online networks in Egypt harvest social capital during the Covid-19 pandemic?”. Key informant interviews discovered that the services provided during Covid-19 pandemic ranged from Personal Protective Equipment to front-line medical personnel to helping those who became unemployed. Study findings showed that social capital has played a major role in establishing social resources, such as trust, norms and values that mobilized networks into action. The strengthening of social capital has also been characterized by strong online presence within the domain of social media platforms that empowered these unofficial networks to act as an informal communication and information channel in times of crisis and uncertainty of the pandemic. Further research would suggest the need for a more in-depth assessment of social capital in the Egyptian context, as well as devising further tools on how to formalize these networks in order to optimize social capital in times of crisis.